The Influence of ISO 31000 on Risk Culture: A Systematic Literature Review - Olivia Putri Zahrani; Isnuhardi Isnuhardi (BUGIS : Journal of Business, Technology, & Social Science, 2026)
This study aims to provide a synthesis of the relationship between ISO 31000 and risk culture. Using a Systematic Literature Review (SLR) approach, the study examines how ISO 31000 influences organizational risk culture. The review is based on 20 journal articles indexed in Scopus (Q1–Q4). The findings indicate that the impact of ISO 31000 on risk culture is mixed. However, 16 out of 20 studies (80%) report a positive influence, particularly when supported by strong top management commitment, leaders’ emotional intelligence, and integration with strategic planning. In addition, key determinants of a risk-aware culture—such as accountability, effective communication, a common risk language, incentive systems, and continuous training—play a significant role in strengthening the relationship between ISO 31000 implementation and risk culture.